Creatinine- and Cystatin C-Based Incidence of Chronic Kidney Disease and Acute Kidney Disease in AKI Survivors. (27th September 2018) - Rimes-Stigare, Claire; Ravn, Bo; Awad, Akil; Torlén, Klara; Martling, Claes-Roland; Bottai, Matteo; Mårtensson, Johan; Bell, Max
Abstract : Background . Renal dysfunction after acute kidney injury (AKI) is common, potentially modifiable, but poorly understood. Acute kidney disease (AKD) describes renal dysfunction 7 to 90 days after AKI and is determined by percentage change in creatinine from baseline. Chronic kidney disease (CKD) is defined as the estimated glomerular filtration rate (eGFR) less than 60 ml/min/1.73 m 2 persisting for more than 90 days . We compared CKD incidence using both creatinine- and cystatin C-based GFR with AKD incidence at 90 days in AKI survivors. Methods . A prospective cohort study was conducted in a Swedish intensive care unit (ICU) between 2008 and 2010. We included AKI patients alive at 90 days. We excluded patients <18 and >100 years, death before follow-up, CKD prior to admission, and follow-up before 60 days or beyond 270 days. Creatinine and cystatin C were measured at 90 days and converted to eGFR (mL/min/1.73 m 2 ). Results . We included 274 patients. At 90-day follow-up, the median creatinine eGFR (MDRD) was 81.6 (IQR 58.6–106.8) and median cystatin C eGFR was 51.5 (IQR 35.8–70.7). The incidence of CKD (eGFR < 60) was 25.8% based on creatinine but 63.7% using cystatin C estimates. AKD was present in 47 patients (18.9%). Age, discharge cystatin C, creatinine at discharge, and female gender predicted creatinine-defined CKD at follow-up. Age, discharge cystatin C, CRRT on ICU, and diabetes were associated with cystatin C-based CKD. Conclusions . In AKI survivors followed up at 3 months, CKD criteria were met in a quarter of patients using creatinine and in two-thirds using cystatin C eGFR. Less than one-fifth of patients fulfilled AKD criteria. The application of AKD criteria may underestimate renal dysfunction in AKI survivors.